Protective Function of Lipid Rafts - I.S. Kapustina (University of Guilan, 2021)
The study of lipid rafts allowed us to take a new look at the morphology, organization and functioning of membranes, both of animal and plant origin. However, lipid rafts and their function in the cell membranes of plants are poorly understood in comparison with the membranes of animal cells. The protective function of the plant cell is of great importance for the body as a whole because plants lead an attached mode of life. To date, it is known that lipid rafts are involved in the membrane mechanisms of cell protection in response to negative effects. In this review, we summarized the literature data showing the participation of lipid rafts of plant membranes (plasmalemma, Golgi complex membranes, chloroplasts, mitochondria, and vacuoles) in the protective function of cells.